Impact of Alexandra Township on the water quality of the Jukskei River - Matowanyika, Wadzanai (My University, 2011)
Accommodation shortage in Alexandra Township, South Africa, has resulted in the establishment of informal settlements on any open land including Jukskei River banks. The closely built dwellings among several other factors have made refuse removal difficult and sanitation facilities inadequate, hence waste including human excreta is discharged on open lands or into the Jukskei. These wastes affect the water quality of the Jukskei River. This study, therefore, determined the changes in water quality as the Jukskei River flowed past Alexandra. Eleven physical, chemical and microbiological parameters were monitored between May and December 2009 at four sites in the Jukskei catchment using standard methods. Water entering Alexandra was only significantly high in turbidity (27.1 ± 4.5 NTU) while water exiting Alexandra contained significantly high pH (7.7 ± 0.1), nitrate (0.36 ± 0.07 mgN/l) and orthophosphate (0.41 ± 0.17 mgP/l). There was no statistical difference in Escherichia coli in the water upstream and downstream of Alexandra. The high nitrate-N, orthophosphate and E. coli downstream of Alexandra were likely to be associated with raw sewage, domestic and animal waste. Most measured parameters in water exiting Alexandra were within the acceptable ranges of aquatic ecosystems guidelines. Ammonium-N and electrical conductivity, however, fell into the bad categories of the aquatic and domestic guidelines respectively. E. coli concentrations were above the drinking water (0 cfu/ml) and recreational (<1.3 cfu/ml) guidelines. Turbidity and total suspended solids were significantly higher in the wet season than in the dry season while orthophosphate, suspended particulate organic matter, pH and electrical conductivity were higher in the dry season at all sites. The changing seasons had no significant influence on temperature, nitrate-N and dissolved oxygen at all the sites. The results suggest that some activities like poor waste disposal in Alexandra can reduce the water quality of the Jukskei River.